The impact of social networks in health - Φακιολάς Νίκος (The Greek Review of Social Research, 2012)
In this article, part of a wider research conducted by NSCR, (ΕΚΚΕ), with the title «Aging and Health» is focused on the relationship between social networks and individual health. An index of conditional social networks is created in order to examine in what extent they support human health, the self- evaluation of health and the use of social services of the individual. The index is created on the basis of the marital status, the relationship with their children, their working condition and, finally, unexpected economic or health problems. It is an effort to understand the perspectives of facing health problems through the positive score in this index. The form and the functioning of social networks play a substantial role in shaping health and the use of health services.